The ocular crisis: Conjunctivitis in Karachi - Muhammad Farhan; Sadia Tahir; Faiza Ahsan (Journal of the Pakistan Medical Association, 2024)
Dear Editor, Conjunctivitis, commonly referred to as Pink Eye, is an eye condition characterized by inflammation of the conjunctiva, leading to a pink or red discoloration due to dilated conjunctival blood vessels. It can progress to hyperemia and swelling with varying discharges. The condition is caused by two main types of agents: viruses and bacteria, termed infective conjunctivitis. Non-infective conjunctivitis is caused by factors such as allergens, toxins, inflammation from immune-related diseases, and neoplastic processes [1]. The best way to diagnose conjunctivitis in a patient is by taking a focused ocular history, followed by a penlight eye examination [1]. There are distinct signs of both viral and bacterial conjunctivitis, on the basis of which a diagnosis is made. A viral conjunctivitis patient typically experiences mild or no pain, redness in the eye, occasional gritty discomfort with mild itching, watery to serous discharge, and usually, the inflammation affects one eye. Bacterial conjunctivitis is characterized by mild to moderate pain, stinging in the eye, a red eye, mucopurulent discharge, and both eyes are usually affected, with the eyes sticking together. Allergic conjunctivitis, whether infective or not, presents with painless tearing, intense eye itching, redness, watery discharge (sometimes stringy), and typically affects both eyes [2]. The main mode of transmission for viral conjunctivitis is through contact with an infected person. This include contaminated fingers, unsterilized medical equipment, infected swimming pool water, or personal items of a conjunctivitis patient. Bacterial conjunctivitis can be acquired much the same way, through contact with an infected individual [1]. Infective conjunctivitis lacks a definitive treatment, but symptomatic relief can be achieved with topical antihistamines, artificial tears, and cold compresses. Topical antibiotics work effectively for bacterial conjunctivitis cases. Non-infective conjunctivitis can be treated with topical decongestants, antihistamines, mast cell stabilizers, non-steroidal anti-inflammatory drugs, and corticosteroids [1]. Infective conjunctivitis is highly contagious. To prevent its spread, practice frequent hand hygiene, disinfect medical equipment, and isolate infected individuals. Patients with bacterial conjunctivitis should avoid cross-contamination. Healthcare professionals, particularly ophthalmologists, should take precautions. Maintaining proper hygiene, including hand and surface disinfection, is crucial to reducing the disease’s burden [3]. Age, sex, and seasonal variations all impact the occurrence of pink eye, which varies among groups [4]. Approximately 15–40% of episodes of pink eye occur due to allergic conjunctivitis during the summer and spring. Simultaneously, most bacterial conjunctivitis occurrences occur between December and April [1,4]. —Continue